Study of Isothermal Behaviour of Natural Tunisian Dolomite Under Controlled Pressure of Carbon Dioxide - GALAI, HAYKEL; NAHDI, K.; TRABELSI-AYADI, M. (Asian Journal of Chemistry, 2010)
The first half decomposition of natural Tunisian dolomite sample, was investigated by thermogravimetric measurements and in situ X-Ray diffraction, in controlled CO2 pressure (20 < PCO2 < 500h Pa) and in isothermal conditions (in the temperature range 823-1023 K). The thermograms exhibited two consecutive weight losses, corresponding to fractional conversion ranges of 0-0.2 and 0.2-1. A decelerating effect of was observed only during the second weight loss. In situ X-ray diffraction results indicate that crystal lattice of dolomite undergoes, during the thermal treatment, a dilatation along the c direction, then it decomposes progressively into poor crystalline MgO and a magnesian calcite Mg0.052Ca0.948 CO3. The characterization of the final product using SEM and XPS has shown that MgO could precipitate at the surface of CaCO3.